Preparation of the General Practice Nursing students for first aid provision - Gutienė, Virginija; Juozapavičienė, Rasa; Freimanienė, Aušra; Staniūtė, Vaiva (Slauga. Mokslas ir praktika, 2022)
First aid is an immediate focus in the event of the acute condition or trauma. Early identification of life threatening conditions and more urgent help providing reduces the mortality rate.The aim of the study – to reveal the readiness of the students of the General Nursing Practice study program to provide first aid.Research methods. Literature analysis was performed. The qualitative research method was chosen.Results. The study shows that students lack theoretical and practical knowledge to initiate resuscitation procedures to infants and children with trauma and massive bleeding. It was found that the initial resuscitation of adults has been sufficiently practiced in the training process, but most of the students do not trust their knowledge of the AED use. Most of the students rate their knowledge to be average, lacking practical knowledge and skills to achieve a good grade. The study also revealed that most of the students can provide first aid correctly, but only a small percentage of students noted very precise actions.Conclusions. It is estimated that the students are moderately confident in their knowledge of initial resus citation and needed actions to prevent choking in adults. However, they lack developed skills in dealing with traumas and acute conditions. According to the students, during the learning process, they lacked theoretical and practical knowledge in the cases of initial resuscitation and bleeding of infants and children. General nursing practice students are most motivated to provide first aid by professional motivation and internal factors. For some students providing first aid is made more difficult by the feeling of confusion and fear. In the end of teaching process of the first aid study subject, the students evaluated their knowledge as average.
Keywords: first aid; basic life support; knowledge; cardiac arrest; AED; ambulace